Hubungan Kadar SGOT dengan Kadar Leukosit pada Pasien NSTEMI di ICCU RSD dr. Soebandi Jember (Correlation between SGOT Level and Leukocytes in NSTEMI Patients at ICCU dr. Soebandi Hospital, Jember) - Finty Arfian; Suryono Suryono; Rini Riyanti (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Acute Coronary Syndrome (ACS) is a syndrome that occurs because of blockage of the coronary artery causing clinical symptoms due to unfulfilled oxygen supply. Atherosclerosis is suspected as the main cause of ACS. Inflammation is one pathophysiology of atherosclerosis characterized by leukocytosis. NSTEMI is one spectrum of ACS that diagnosed by anamnesis, ECG, and cardiac marker such as troponin. SGOT is also released into the circulation when there is myocardial damage. Studies has reported that SGOT increased from the normal range during a myocardial infarction. The purpose of this study was to determine the relationship between levels of SGOT and leukocytes in patients with NSTEMI. The sample included 10 patients with NSTEMI in July-December 2016 from ICCU RSD dr. Soebandi Jember. The data was collected from medical record. The result showed that the average of SGOT increased from the normal range, while the average levels of leukocytes were in normal range. Pearson correlation test showed that there was no significant relationship between the two variables with p=0.083>0.05. In conclusion, there was no relationship between the levels of SGOT and leukocytes in patients with NSTEMI at ICCU RSD dr. Soebandi Jember. Keywords: NSTEMI, SGOT, Leukocyte